Teaching Quality Improvement Through a Book Club - Benjamin Doolittle; Jaideep Talwalkar (Tabriz University of Medical Sciences, 2015)
Introduction: Quality Improvement projects are an important part of residency education in the United States and are required for accreditation by the Accreditation Council for Graduate Medical Education. Participation in standard chart-based quality improvement had failed to generate excitement among residents in our program. The objective of our innovation was to inspire interest in quality improvement among our residents. Methods: Our residency program instituted a book discussion group. Attendance and participation of attendees was recorded, and residents were sent a follow-up survey one month after the activity to gauge their impressions. Results: Out of 16 residents in the program, 12 attended the discussion group, and all attendees participated in the discussion. The follow-up survey revealed that 10/11 (91%) of respondents had read at least part of the book and 11/11 (100%) wanted to have another book discussion group in the upcoming year. Conclusion: We believe that the use of a book discussion group can be a novel, inspiring strategy to teach quality improvement in a residency program.